Preventive effects of geraniol in schizophrenia-like symptoms in mice models of psychosis - Uruaka, Christian I.; O. Georgewill, Udeme; Georgewill, Owunari A. (International Journal of Research in Medical Sciences, 2023)
Background: The pathogenesis of schizophrenia has been linked to N-methyl-D-aspartate receptor (NMDAr) inhibition and DAr hyperfunction. Geraniol is a naturally occurring acyclic monoterpene with diverse pharmacological applications. We aimed to assess the effect of geraniol on schizophrenia-like symptoms, vis a vis its modulatory actions on neurochemicals in mice models of psychosis. Methods: In acute studies, male Swiss mice (n=5/group) were intraperitoneally treated with geraniol (25, 50 and 100 mg/kg), risperidone (0.5 mg/kg) or vehicle (10 ml/kg) prior to ketamine (KET) (10 mg/kg)-induced stereotypy and hyperlocomotion. In the chronic studies, mice (n=7/group) were exposed to 14 days interventions (geraniol or risperidone) following a preventive treatment with KET (20 mg/kg) from days 7-14 consecutively. The effects of treatments (e.g., geraniol or risperidone) alone and on KET-induced schizophrenia-like symptoms were investigated on the last day, 24 hours after treatments. Following that, neurochemical and neurotrophic alterations in the brain (striatum, prefrontal cortex, and hippocampus) tissues were investigated. Results: Intoxication with KET was associated with schizophrenia-like symptoms as evidenced by stereotypy behavior and hyperlocomotion. KET further induced hyperlocomotion, behavioral despair, and cognitive impairment in the chronic studies. It altered the levels of dopamine, 5-hydroxytrypamine, glutamic acid decarboxylase (GAD), acetylcholinesterase (AChE), and brain-derived neurotrophic factor (BDNF) in brain tissues. However, GER (50 and 100 mg/kg) administration significantly prevented the brain's insults caused by KET. Conclusions: Altogether, the findings support geraniol's neuroprotective activity while also adding to the body of knowledge that geraniol inhibits schizophrenia-like symptoms via modulation of neurochemical and neurotrophic pathways.